'Are we on the same wavelength?' International nurses and the process of confronting and adjusting to clinical communication in Australia. (13th February 2017) - Crawford, Tonia; Roger, Peter; Candlin, Sally
Abstract : Effective communication skills are important in the health care setting in order to develop rapport and trust with patients, provide reassurance, assess patients effectively and provide education in a way that patients easily understand (Candlin and Candlin, 2003). However with many nurses from culturally and linguistically diverse (CALD) backgrounds being recruited to fill the workforce shortfall in Australia, communication across cultures with the potential for miscommunication and ensuing risks to patient safety has gained increasing focus in recent years (Shakya and Horsefall, 2000; Chiang and Crickmore, 2009). This paper reports on the first phase of a study that examines intercultural nurse patient communication from the perspective of four Registered Nurses from CALD backgrounds working in Australia. Five interrelating themes that were derived from thematic analysis of semi-structured interviews are discussed. The central theme of 'adjustment' was identified as fundamental to the experiences of the RNs and this theme interrelated with each of the other themes that emerged: professional experiences with communication, ways of showing respect, displaying empathy, and vulnerability.